Fabrication and evaluation of silica aerogel-epoxy nanocomposites: Fracture and toughening mechanisms. (October 2018) - Salimian, Saeed; Malfait, Wim J.; Zadhoush, Ali; Talebi, Zahra; Naeimirad, Mohammadreza
Highlights: Aerogels can improve the mechanical properties of epoxy-based nanocomposites due to 3-dimensional nanoporous structure and high surface area. The effect of silica aerogel was investigated on the rheological, mechanical and thermal properties of the epoxy nanocomposite. Two main toughening mechanisms are identified: (a) crack pinning and deflection, and (b) plastic deformation (debonding). Abstract: Silica aerogel is a promising candidate for improving the mechanical properties of epoxy-based nanocomposites due to the unique properties such as the 3-dimensional nanoporous structure and high surface area. In this study rheological, mechanical and thermal properties of the silica aerogel-epoxy nanocomposites were investigated. The rheological results demonstrated an increase in viscosity of the nanocomposite suspension compared to the neat resin. The results of dynamic mechanical along with the thermal analysis showed that the addition of 6 wt% of silica aerogel causes the storage modulus and glass transition point (Tg) to be increased by 11% and 5 °C, respectively. Also, significant improvements in the elastic modulus (35%), tensile strength (62%) and toughness (126%) were achieved with the optimal volume fraction of silica aerogel (6 wt%). Two main fracture mechanisms were involved in the fracture behavior of the silica aerogel-epoxy nanocomposite: (a) crack pining and deflection, and (b) plastic deformation (debonding).